2021
DOI: 10.1182/bloodadvances.2021004352
|View full text |Cite
|
Sign up to set email alerts
|

Suboptimal iron deficiency screening in pregnancy and the impact of socioeconomic status in a high-resource setting

Abstract: Iron deficiency anemia (IDA) in pregnancy is associated with poor maternal and childhood outcomes, yet ferritin testing, the standard test for iron deficiency (ID), is not considered part of routine prenatal bloodwork in Canada. We conducted a retrospective cohort study of 44,552 pregnant patients with prenatal testing at community laboratories in Ontario, Canada to determine the prevalence of ferritin testing over five years. Secondary objectives were to determine the prevalence and severity of ID, and to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 32 publications
5
41
0
Order By: Relevance
“…A Canadian study performed in a high-resource setting found that screening for iron deficiency was missed in 40% of pregnancies. 18 Our study found similar trends in lack of screening through laboratory tests.…”
Section: F I G U R E 2 Broken Down By Trimester(s)supporting
confidence: 82%
See 1 more Smart Citation
“…A Canadian study performed in a high-resource setting found that screening for iron deficiency was missed in 40% of pregnancies. 18 Our study found similar trends in lack of screening through laboratory tests.…”
Section: F I G U R E 2 Broken Down By Trimester(s)supporting
confidence: 82%
“…As such, appropriate screening to identify iron deficiency is imperative for early prevention. A Canadian study performed in a high‐resource setting found that screening for iron deficiency was missed in 40% of pregnancies 18 …”
Section: Discussionmentioning
confidence: 99%
“…This corresponds to a progressive rise in gestational IDA in the first, second, and third trimesters: 2.7%, 2.2%, and 10.8%, respectively [ 3 ]. However, a recent survey showed an increasing trend of gestational ID (23.8%) in the first trimester in 2021 [ 4 ]. Gestational IDA is associated with the risk of maternal mortality and both cognitive and behavioral abnormalities of neonates [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to dietary access, Teichman et al identified that ferritin screening was significantly lower between high‐ and low‐income households (odds ratio [OR], 0.83; 95% CI, 0.7‐0.9). These data suggest that individuals with low income are less likely to be screened for ferritin deficiency in pregnancy, which delays the diagnosis and treatment of iron deficiency and developing anemia 35 …”
Section: Types Of Anemiamentioning
confidence: 99%
“…These data suggest that individuals with low income are less likely to be screened for ferritin deficiency in pregnancy, which delays the diagnosis and treatment of iron deficiency and developing anemia. 35 Additional clinical considerations include chronic inflammation and infection during pregnancy, as these may falsely elevate ferritin levels used to screen for iron deficiency anemia. In these situations, TSAT is a more accurate measure of iron storage 22,36 because TSAT levels are less influenced by chronic infections or inflammation.…”
Section: Screeningmentioning
confidence: 99%